PENGARUH MOTIVASI SISWA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA MUHAMMADIYAH WAINGAPU - Rambu Luyang, Putri Nanda; Wadu, Darius Imanuel (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' critical thinking skills in terms of learning motivation at SMA Muhammadiyah Waingapu. The method used in this study is quantitative with a quasi-experimental design involving two classes, namely the experimental class and the control class. The instruments used are critical thinking tests and learning motivation questionnaires. The results of data analysis show that the data is normally distributed and homogeneous. The independent sample t-test shows a significance value of 0.015 (< 0.05), which means there is a significant difference between the critical thinking skills of students taught with the PBL model and the conventional model. The average score of the learning motivation questionnaire is 62.41 out of a maximum score of 80 (78.01%), indicating that students' learning motivation is in the high category. Thus, the PBL learning model is effective in improving students' critical thinking skills, especially for those with high learning motivation. Keywords: Problem Based Learning; critical thinking skills; learning motivation.